2021
DOI: 10.1186/s42077-021-00151-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intrathecal preservative-free midazolam versus nalbuphine as an adjuvant to intrathecal bupivacaine (0.5%) in patients undergoing elective lower-segment caesarean section

Abstract: Background Intrathecal anesthesia is common for parturients undergoing lower-segment caesarean section. Various adjuvants are added to intrathecal bupivacaine for potentiating pharmacological effects, improving quality of sensorimotor block and postoperative analgesia, and preventing adverse effects. The study period was from November 2017 to September 2018, and it was a randomized double-blinded observational study. The sample size calculation was done according to results of our pilot study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…These outcomes agree with earlier studies. 9,19,23 As regard maternal sedation score, current study demonstrated significant differences among the groups with lowest score in Group-B and highest score in Group-M. The results agree with Amin et al who recorded scores of (0.61 ± 0.32 vs 2.75 ± 0.54) in controls and midazolam respectively, (P < 0.001).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These outcomes agree with earlier studies. 9,19,23 As regard maternal sedation score, current study demonstrated significant differences among the groups with lowest score in Group-B and highest score in Group-M. The results agree with Amin et al who recorded scores of (0.61 ± 0.32 vs 2.75 ± 0.54) in controls and midazolam respectively, (P < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…4 Also, Thakkar et al found more sedative effect of intrathecal midazolam than nalbuphine, 18 but others did not. 12,19,22 Apgar scores at 1 min and 5 min after childbirth demonstrated no significant differences among the four groups. There weren't any reported cases of neonatal morbidity or mortality.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations